Las montañas como regiones. La Sierra de El Cuale (Jalisco) en el Occidente de México - Carlos Riojas (Les Cahiers ALHIM)
The objective of our study is to present a case study regarding the reconfiguration of regions in Mexico, and how this example of regional and local policy can respond to changing social contexts and impacts the environmental situation. This study is a proposal made in response to National Council of Forestry’s (CONAFOR spelled in Spanish) call for a regional program that would define ways to achieve sustainable management of the Cuale Highlands in Jalisco. If we consider the multiple dimensions of regional development in Mexico, specifically the territorial and ecological impact in the Central Western region of the country, much of it resulting from pressure brought to bear on the natural resources in the context of economic and institutional reform implemented during the last two decades of the 20th century, we believe that the fundamental conclusion to be drawn is that programs must be developed with a firm commitment to ecological, economic and social sustainability in critical zones, and these programs must propose solid mechanisms of cooperation between the public, private and social sectors in order to come up with comprehensive solutions.